Temi e problemi della storiografia sul monachesimo latino nel Mezzogiorno dei secoli XI-XIII - Galdi, Amalia (Quaderni di storia religiosa medievale, 2019)
Latin monasticism, in all its aspects, has been one of the most widely studied historiographical subjects concerning Southern Italy during recent decades. New sources and new hermeneutic levels have made it possible to know more about this topic and, in particular, its peculiarities and its “inclusionµ within the Italian and European monastic context. This essay proposes a status quaestionis on the research into this subject and the historiographical discussion, which involves especially some monastic institutions (such as SS. Trinità di Cava, S. Maria di Montevergine and S. Maria di Pulsano) in Southern Italy from the 11th to the 13th century. In point of fact, they are characterized by common paths, such as their origins, yet also by later, different developments.